1997
DOI: 10.1080/01652176.1997.9694756
|View full text |Cite
|
Sign up to set email alerts
|

Pathological changes in metabolism of poultry related to increasing production levels

Abstract: SUMMARYA continuously increasing production level in poultry breeding has resulted in changes in metabolism.Selection procedures in breeding programmes are focused on an increase in growth rate and on a decrease in feed conversion ratio (less feed intake per unit of deposited tissue). These procedures do not pay attention to the maintenance requirements of birds. Imbalances between production (protein and fat deposition) and supply of energy for maintenance requirements lead to homeostatic dysregulation and to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
28
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(30 citation statements)
references
References 15 publications
0
28
0
2
Order By: Relevance
“…In addition, the CTR chickens had better FCR than the AMT birds during the finishing phase, possibly due to the improved feed efficiency during compensatory growth when the tibias of the CTR chickens were recovering from day 20 to day 34 (Zubaira and Leeson, 1996). Scheele (1997) noted that the growth of the pectoral muscles primarily occurs during the late stages of developmental growth in fast-growing birds. In the present study, an increased slaughter yield was also observed in the treated group, suggesting that the relatively rapid growth of the AMT-fed chickens in the grower and finisher phases may have contributed to the comparable increases in carcass and breast muscle yields.…”
mentioning
confidence: 99%
“…In addition, the CTR chickens had better FCR than the AMT birds during the finishing phase, possibly due to the improved feed efficiency during compensatory growth when the tibias of the CTR chickens were recovering from day 20 to day 34 (Zubaira and Leeson, 1996). Scheele (1997) noted that the growth of the pectoral muscles primarily occurs during the late stages of developmental growth in fast-growing birds. In the present study, an increased slaughter yield was also observed in the treated group, suggesting that the relatively rapid growth of the AMT-fed chickens in the grower and finisher phases may have contributed to the comparable increases in carcass and breast muscle yields.…”
mentioning
confidence: 99%
“…**P < 0.01; ***P < 0.001. whereas leg muscle was not affected at 42 days of age. Scheele (1997) noted that growth occurs primarily in the pectorals and feather during the late stages of development in fast-growing broilers. The relatively rapid growth in PQQ.Na 2 -fed chicks in the grower phase may partly contribute the comparable increase of breast muscle yield.…”
mentioning
confidence: 99%
“…In Australia, approximately 55% of eggs are produced in cage layer farms, with the balance coming from barn (9%) and free-range (34%) farms (AECL, 2011). It has been recognised that, typically, metabolic disorders such as FLHS cause loss to the industry through reduced productivity and increased mortality (Julian, 2005;Leeson, 2007;Scheele, 1997). Taking in consideration that more than 50% of Australia's layer flocks are caged, the investigation of the effect of housing system on causes of mortality in laying hens is of economic and ethical importance for Australian poultry industry.…”
Section: Data Processing and Statistical Analysismentioning
confidence: 99%
“…High producing birds within a flock are most often affected by FLHS (Scheele, 1997), most probably due to a relationship between energy metabolism and hormone levels during egg production. Oestrogens influence lipid synthesis which is required for the yolk (Walzem et al, 1999).…”
Section: Hormonal Factorsmentioning
confidence: 99%
See 1 more Smart Citation